Design of Auto Cut Off Charging System for Electric Car Battery of Untan Electrical Car Team Based on ESP-32 Microcontroller - Hasan, Muhammad (Faculty of Engineering, Universitas Tanjungpura, 2024)
Battery charging is the process of charging a battery from low to full capacity. In this study, the battery used is an 18650 48V 21Ah lithium-ion battery that is charged using an 18650-lithium charger that has an auto cut off feature when the battery is full. This feature is important to prevent overcharging and overcurrent, which can damage the battery. However, this charger is not equipped with a temperature sensor and cannot display voltage and current values. Monitoring the temperature, voltage, and current is very important, especially since battery temperatures exceeding 60 °C can cause damage and risk fire. Charging the battery to 80-90% of full capacity can also extend battery life by reducing chemical degradation. The system developed in this research includes an auto cut off feature that is activated based on temperature, a voltage regulated between 47.1V to 53.5V, and control via IoT Blynk. The system uses ESP-32 as the microcontroller, MAX6675 thermocouple temperature sensor, PZEM-017 sensor for DC voltage and current, and 16x2 LCD keypad shield to set the set point and display the sensor results. The results show that auto cut off works well, with voltage sensor accuracy reaching 99.85% and PZEM-017 sensor accuracy of 97.68%.